1980
DOI: 10.1002/oca.4660010403
|View full text |Cite
|
Sign up to set email alerts
|

Application of an advanced trajectory optimization method to ramjet propelled missiles

Abstract: SUMMARYThe mission performance characteristics of ramjet-propelled missiles are highly dependent upon the trajectory flown. Integration of the trajectory profile with the ramjet propulsion system performance characteristics to achieve optimal missile performance is very complex. Past trajectory optimization methods have been extremely problem dependent and require a high degree of familiarity to achieve success. A general computer code (CTOP) has been applied to ramjet-powered missiles to compute open-loop opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Even though straightforward in implementation, simplification‐based methods cannot fully reflect the characteristics of the air‐breathing vehicle or obtain the optimality of the optimal solution. These drawbacks are overcome by the optimal control theory, which has been widely applied in trajectory optimization problems . Lu et al demonstrated that the finite difference method is well suited for calculating optimal ascent trajectories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though straightforward in implementation, simplification‐based methods cannot fully reflect the characteristics of the air‐breathing vehicle or obtain the optimality of the optimal solution. These drawbacks are overcome by the optimal control theory, which has been widely applied in trajectory optimization problems . Lu et al demonstrated that the finite difference method is well suited for calculating optimal ascent trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks are overcome by the optimal control theory, which has been widely applied in trajectory optimization problems. [14][15][16][17][18] Lu et al 19 demonstrated that the finite difference method is well suited for calculating optimal ascent trajectories. In the work of Murillo and Lu,20 the original problem is reduced to a series of root-finding problems and solved by a finite difference algorithm.…”
mentioning
confidence: 99%